Commoning Water: Co-creating Knowledge and Institutions for Conjunctive Use of Water: A case from India - Singh, Subrata; Priyadarshini, Pratiti; Meinzen-Dick, Ruth S.; Mohanty, Ranjit; Falk, Thomas (2021)
Prepared by: Subrata Singh, Pratiti Priyadarshini, Ruth Meinzen-Dick, Ranjit Mohanty, Thomas Falk